STRUCTURE AND COMPONENTS OF MILITARY-PROFESSIONAL COMPETENCE (Conferencea, 2022)
The components of the development of military-professional competence of a pre-call up military teacher, the basic competencies aimed at further improving the military pedagogical skills of future specialists in the provision of basic military knowledge are described.